Estradiol administration modulates neural emotion regulation. (December 2021) - Rehbein, Elisa; Kogler, Lydia; Hornung, Jonas; Morawetz, Carmen; Bayer, Janine; Krylova, Marina; Sundström-Poromaa, Inger; Derntl, Birgit
Abstract: Variations of sex hormones during the menstrual cycle can lead to changes in emotion processing. The ability to successfully regulate one's emotions is associated with better social abilities and mental health. While women show better performance in fear extinction learning under high estradiol (E2) compared to women under low E2 levels, little is known about the effect of E2 on emotion regulation. We explored whether E2 modulates emotion regulation in a functional magnetic resonance imaging paradigm and administered E2 valerate to 32 young naturally cycling women during their early follicular phase in a double-blind, placebo-controlled within-subject design. This standardized experimental control allowed us to explore the specific effect of E2 on emotion regulation while controlling for other hormones varying throughout the menstrual cycle. Behaviorally, no difference between conditions appeared. However, on the neural level, E2 administration was associated with lower activation in the right lingual- and left calcarine gyrus, right orbitofrontal cortex and left hippocampus relative to placebo. With respect to the main effect of down-regulation higher activation of the right superior frontal gyrus and left dorsomedial prefrontal cortex was seen; which is in accordance to previous literature. An interaction between drug condition and emotion regulation appeared for the left inferior frontal gyrus extending into the middle frontal gyrus indicating lower activation during down-regulation in the E2 condition than the placebo condition. On the behavioral level, women reported less negative affect in the E2 condition. The results fit well to a previously described psychoneuroendocrinological model in which E2 plays an important modulatory role on emotional processes and risk factors of mental health in women. Highlights: E2 or placebo was administered in a double-blind, repeated-measures design. Women performed a negative emotion regulation fMRI task twice. Women reported less negative affect in the E2 condition. Less neural activation in the E2 condition during down-regulation. E2 plays a modulatory role in neural emotion regulation.